Formulasi Sediaan Deodoran Spray dengan Ekstrak Lidah Buaya: Penelitian - Rahmi Mudia Alti; Intan Cynara Valentina Putri; Rifka Agustianti (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This study aimed to formulate a deodorant spray using alum and aloe vera extract as natural antibacterial agents. An experimental laboratory method was applied with three formula variations. Evaluations included organoleptic properties, homogeneity, pH, initial stability, and skin irritation tests. The results showed that Formula 2 (5% alum, 8% aloe vera extract) exhibited the best physical stability, a pH closest to normal skin (6.2), and caused no irritation among volunteers. Formula 1 showed similar results but had a slightly lower pH performance, while Formula 3 exhibited visual instability and one mild irritation case. Formula 2 was selected as the optimal formulation, fulfilling all evaluation parameters. Further research is recommended to conduct long-term stability testing and antibacterial effectiveness assessments to support product development as a safe and effective natural deodorant spray.